Hedging the Health of the Poor : The Case for Community Financing in India - Gumber, Anil (World Bank, Washington, DC, 2013)
This paper reviews the existing community-based and self-financing health insurance schemes in India catering to the general population as well as addressing the needs of the poor and vulnerable section of the society. Also discussed are some critical issues of accessibility and use of health care services, out-of-pocket expenditure on treatment and the need for health insurance for poor households pursuing varied occupations in both rural and urban areas. The paper examines in detail the determinants of enrollment in the community-based financing scheme, using the household-level data from the pilot study undertaken in Gujarat (India). It also investigates the issue of how much health insurance mitigates the households' burden of health care expenditure. The findings suggest that the community plan fairly addresses equity in enrollment but that, in terms of providing financial